1975
DOI: 10.1172/jci108174
|View full text |Cite
|
Sign up to set email alerts
|

The perturbation of thrombin binding to human platelets by anions.

Abstract: ABSTRA CT Thrombin binds with high affinity to specific cell-surface receptors on washed human platelets. We present experiments indicating that thrombin binding correlates with the release reaction when binding is perturbed by anions. Marked differences in the affinity of human "I-thrombin for platelets were observed in various isotonic buffers at pH 7.4. At low concentrations of thrombin (0.001-0.01 U/ml), binding was 5-fold greater in Tris-sodium acetate and 12-fold greater in Tris-sodium cacodylate than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…The number of binding sites on the platelet surface calculated from our data is slightly higher than the number reported in some previous studies (12,14,15). This is very likely due to the presence of cacodylate in the buffers used in the binding studies reported here, as has been shown previously (28). The total number ofthrombin molecules bound at saturation was not changed by factor D, whereas the apparent KdiSS for thrombin was increased, which indicates competitive inhibition.…”
Section: Inhibition Of Platelet Aggregation With Factor D)supporting
confidence: 71%
“…The number of binding sites on the platelet surface calculated from our data is slightly higher than the number reported in some previous studies (12,14,15). This is very likely due to the presence of cacodylate in the buffers used in the binding studies reported here, as has been shown previously (28). The total number ofthrombin molecules bound at saturation was not changed by factor D, whereas the apparent KdiSS for thrombin was increased, which indicates competitive inhibition.…”
Section: Inhibition Of Platelet Aggregation With Factor D)supporting
confidence: 71%
“…Human alpha and gamma thrombin were prepared as described previously (11,19,20 [1251]thrombin was used the same day of preparation and the DIP-thrombin over a period of 3 wk. Acid soluble collagen was a gift from Mr. Heinz Scheuenstuhl.…”
Section: Methodsmentioning
confidence: 99%
“…Platelets (0.2 ml) were membrane filtered and the retained pH]serotonin was measured in a liquid scintillation counter. Gross counts per minute were corrected for 125I using 1251 standards which were counted by beta and gamma scintillation spectrometry (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombin binds specifically and reversibly to high affinity receptors on the platelet surface (5)(6)(7)(8). There is good evidence to suggest that binding muist occur before secretion can take place (8,9). Although secretion does not occur if the active site of thrombin is blocked (4), the lack of thrombin turnover anid the requirement for a threshold concentration of thrombin before release can occur (10) suggest that the thrombin-induced release is not a simple enzymatic process.…”
Section: Introductionmentioning
confidence: 99%